2012
DOI: 10.1071/bt12051
|View full text |Cite
|
Sign up to set email alerts
|

Climate constraints on growth and recruitment patterns of Abies faxoniana over altitudinal gradients in the Wanglang Natural Reserve, eastern Tibetan Plateau

Abstract: The radial growth and recruitment patterns of trees in subalpine areas are subject to the influence of changing environmental conditions associated with changes in elevation. To investigate responses of fir radial growth and recruitment to climate factors at different elevations, tree-ring width chronologies and age structures of Abies faxoniana were developed from five sampling sites at ~2800–3300 m elevation on the north-western and south-eastern aspects in the Wanglang Natural Reserve on the eastern edge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…7) may be the most limiting aspect of climate on growth for conifer species in JNNR. In a study on A. fargesii (AKA A. faxoniana ) from the nearby Wanglang Nature Reserve, Zhao et al [46] similarly concluded that growth was negatively correlated with temperature during the previous growing season (they also found a positive correlation with precipitation in January, as we did). Previous studies have emphasized the importance of temperature during winter, fall and spring in limiting radial growth, but also observed non-significant negative correlations or response functions between growth and summer temperatures [42], [43].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…7) may be the most limiting aspect of climate on growth for conifer species in JNNR. In a study on A. fargesii (AKA A. faxoniana ) from the nearby Wanglang Nature Reserve, Zhao et al [46] similarly concluded that growth was negatively correlated with temperature during the previous growing season (they also found a positive correlation with precipitation in January, as we did). Previous studies have emphasized the importance of temperature during winter, fall and spring in limiting radial growth, but also observed non-significant negative correlations or response functions between growth and summer temperatures [42], [43].…”
Section: Discussionsupporting
confidence: 74%
“…Despite our low correlation between growth and precipitation, drought stress likely has an impact on growth of trees in the region. Several studies from central and SE China have shown high correlations between Palmer Drought Severity Index (PDSI) and growth [5], [8], [43], [46]. Also, growth of P. tabuliformis has been shown to be sensitive to drought in northern China [6], [44], [45].…”
Section: Discussionmentioning
confidence: 99%
“…The average temperature is 11~17.5°C in July and −6~1°C in January. The mean annual precipitation is around 1100 mm (Zhao et al 2012 (Taylor et al 2006).…”
Section: Study Sitementioning
confidence: 99%
“…Besides, the number, height, and recruitment microsites (bare soil bed, moss-cover ground, decaying logs, or stumps) of A. faxoniana seedlings and saplings, as well as the number, coverage, and height of F. denudata, were counted in each plot. A. faxoniana seedlings or saplings were classified as follows: seedlings, ≥10 and <50 cm in height; saplings, ≥50 cm in height and <5 cm in DBH (Zhao et al 2012). A total of 103 gaps were recorded in the studied area, ranging from 20 to 1860 m 2 in size and 2-60 years in age, and a total of 515 plots were recorded.…”
Section: Plot Setting and Samplingmentioning
confidence: 99%
See 1 more Smart Citation